Chinese Experts′ Consensus on the Management of Hypothalamic Obesity Secondary to Sellar Lesions - Hypothalamic and Pituitary Disease Group of China Alliance for Rare Diseases (罕见病研究)
Obesity is a common complication of sellar lesions. The treatment of the disease is a great challenge to the physicians. To promote effective management for hypothalamic obesity secondary to sellar lesions, our team developed this consensus based on the latest research and clinical experiences in China. We summarized the clinical characteristics and diagnostic criteria for hypothalamic obesity. Using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system, we provided practical recommendations for the screening, clinical evaluation, and comprehensive management of hypothalamic obesity secondary to sellar lesions. Specifically, we recommend examining the body mass index and evaluating endocrine and non-endocrine functions of the hypothalamus to screen out the hypothalamic obesity in patients whose sellar lesions and their treatment involving the hypothalamus, and in obese patients who have hypothalamic or pituitary dysfunction. Meanwhile, we recommend evaluating metabolic complications and primary diseases, too. Furthermore, we recommend that lifestyle interventions be strengthened to patients with hypothalamic obesity, coupled with administering weight-losing drugs or bariatric surgery when necessary, and taking appropriate hormonal replacement for hypopituitarism.